Risk Factors as an Indicator of Non-Complications Spontaneous Preterm Birth: a Study in Eight Hospitals - Sriyana Herman (Ektodermal Displazi Grubu, 2020)
To determine the indicator and identify risk factors for noncomplicated spontaneous preterm birth. A case-control study analysis on 276 mothers after spontaneous preterm and aterm birth were eight hospitals in Indonesia. Among 28 risk factors, we found six most significant risk factors including a novel indicator, Edinburgh Postnatal Distress Scale (OR 6.66, CI 95%:1.36-32.56, p <0.001 for a severe score >13 and OR 6.15, CI 95%:2.06-18.34, p <0.001 for moderate score 10-12). The difference with previous publications, the number of children especially primipara had a significant risk to occur preterm birth (OR 3.77, CI 95%:1.79-7.92, p <0.001), in addition to multipara (OR 7.01, CI95%:3.06-16.05, p <0.001). We also determined that the mother have weightlifting work >5 hr/day (OR 5.41, CI 95%:2.33-13.54, p<0.000), low social economy status (OR 2.70, CI 95%:1.40-5.19, p.0.003) and Mid Upper Arm Circumference <23.5 cm (OR 3.71, CI 95%:1.30-10.53, p<0.014) were the indicators. The highest OR to occur preterm birth was a history of ever 1-2/>2 times preterm birth (OR 16.26, CI 95%:1.71-154.37, p<0.015). We revealed the six indicators of risk factors for a spontaneous preterm birth that may help decision-making in determining an early intervention that measures in both early treatments.